The Association of rs2114358 in the miR-1206 Polymorphism to Chronic Myeloid Leukemia - Hassan, Fathelrahman M. (MicroRNA, 2019)
Introduction: Association studies with factor candidates have advised that single nucleotide polymorphisms (SNPs) could also be related to CML progression and to the response to medical care. Genetic variation in miR-1206 of both derived and neighborhood SNPs process genes will contribute to the predisposition to cancer. The role of those with the risk of CML has not been extensively studied. Therefore, the aim of this study was to evaluate whether polymorphisms in rs2114358 in pre-miRNAs process genes contribute to the risk of CML. Methods: A cross-sectional study was conducted during the period of March 2016 to October 2017 in Khartoum state teaching hospitals. The study population included a total of 420 patients who were previously diagnosed of having CML and 220 cancer-free controls of both gender and were of the same age range. Peripheral blood and bone marrow aspiration samples were collected from patients (254 males, 166 females; median age 58.5 years, range from less than 50 and above 50 years old) and investigated after written informed consent was obtained. Patients were in chronic phase (n=212), accelerated phase (n=125), and blast (n=83). All the patients were under treatment using chemotherapy regiments. The rs2114358 SNP in pre-miRNA was selected for genotyping. Results: The genotyping success rate was 98.3%. Genotype frequencies of the derived SNP and the neighborhood rs2114358 of miR-1206 compared to the controls were significantly different under Hardy-Weinberg Equilibrium (P=0.0001 and 0.0001 respectively). Significant differences were found in allele distributions of this SNP (P<0.01 and P<0.01). In total, the derived variant C allele of rs2114358 (OR=0.168, 95% CI=0.13-0.22) and G allele of neighborhood rs2114358 (OR=0.561, 95% CI=0.44-0.72) in patients' group were associated with an increased risk of CML compared to a control group. Patients with rs2114358 CC genotype (P = 0.0001) or TC (P = 0.0001) and the neighborhood rs2114358 GA genotype (P = 0.0460) or GG (P = 0.0093) were obviously much higher than that of the TT and AA genotype's patients. Conclusion: In conclusion, we discovered the association of SNP rs2114358 in miR-1206 with the risk of CML patients, though more investigations are still required to understand the regulative mechanisms of this miR SNP with the target genes resulting in its dysregulation.
Keywords: CML risk